Analysis of root distribution in 12 citrus rootstocks grown in palmira, the cauca valley (1992)
At the ICA National Research Center in Palmira a study of the root system of 12 rootstocks grafted with "Frost Valencia" orange 14 years old grown on clay-loam soil was conducted. Root samples were taken at distances of 1.0, 1.5, 2.0 and 3.0 m from stem and a depth of 0-20, 20-40, 40-60, 60-80 and 80-100 cm in each distances. The rootstocks Amblycarpa, Citrange Carrizo and Cleopatra Mandarin presented the greater root densities. The height, diameter and the foliage tree volume showed positive correlation whit a diameter lesser than two millimeter. That's special importance for the adaptation several soil's conditions.